A Phosphoproteomic Approach towards the Understanding of the Role of TGF-β in Trypanosoma cruzi Biology - Ferrão, Patrícia M. (Public Library of Science, 2012)
Transforming growth factor beta (TGF-β) plays a pivotal role in Chagas disease, not only in the development of chagasic cardiomyopathy, but also in many stages of the T. cruzi life cycle and survival in the host cell environment. The intracellular signaling pathways utilized by T. cruzi to regulate these mechanisms remain unknown. To identify parasite proteins involved in the TGF-β response, we utilized a combined approach of two-dimensional gel electrophoresis (2DE) analysis and mass spectrometry (MS) protein identification. Signaling via TGF-β is dependent on events of phosphorylation, which is one of the most relevant and ubiquitous post-translational modifications for the regulation of gene expression, and especially in trypanosomatids, since they lack several transcriptional control mechanisms. Here we show a kinetic view of T. cruzi epimastigotes (Y strain) incubated with TGF-β for 1, 5, 30 and 60 minutes, which promoted a remodeling of the parasite phosphorylation network and protein expression pattern. The altered molecules are involved in a variety of cellular processes, such as proteolysis, metabolism, heat shock response, cytoskeleton arrangement, oxidative stress regulation, translation and signal transduction. A total of 75 protein spots were up- or down-regulated more than twofold after TGF-β treatment, and from these, 42 were identified by mass spectrometry, including cruzipain–the major T. cruzi papain-like cysteine proteinase that plays an important role in invasion and participates in the escape mechanisms used by the parasite to evade the host immune system. In our study, we observed that TGF-β addition favored epimastigote proliferation, corroborating 2DE data in which proteins previously described to be involved in this process were positively stimulated by TGF-β.